Surgical correction of persistent truncus arteriosus on a 33-year-old male with unilateral pulmonary hypertension from migration of pulmonary artery band. Issue 1 (December 2016) - Ruan, Wen; Loh, Yee; Guo, Kenneth; Tan, Ju Le
Abstract Background Persistent truncus arteriosus is a rare congenital condition with which survival into adulthood is dismal without surgery. This is the oldest patient reported to our knowledge demonstrating the feasibility of assessing operability in persistent truncus arteriosus with unilateral pulmonary stenosis, and performing full corrective surgery in adulthood. Case presentation We report a Chinese male with successful correction of Type I persistent truncus arteriosus at 33 years of age. He had unilateral pulmonary hypertension from migration of pulmonary artery band from the main to the right pulmonary artery, severe truncal valve regurgitation from previous infective endocarditis, and progressive congestive heart failure. Improvement of lung perfusion was demonstrated 21 months post operation. Conclusion This case demonstrated that in patients with persistent truncus arteriosus and two pulmonary arteries, pulmonary vascular disease or underdevelopment of one lung does not preclude a full corrective surgery so long as the other vascular bed is normal. It is important to emphasize the importance of assessing patient's operability in totality.